EFFECT OF DESCRIPTIVE FEEDBACK AND CORRECTIVE FEEDBACK ON ACADEMIC ACHIEVEMENT OF VII GRADERS IN MATHEMATICS - Ghazala Noureen, Mubashara Akhtar, Riffat un Nisa Awan (PJE, 2023)
Mathematics has become a universal language and a way of thinking especially due to the advancement in the electronic media. Effective teaching plays a vital role in the propagation of mathematical knowledge. Feedback strategies can be used to enhance mathematical understanding. Feedback process helps the students to acquire information about their existing achievement with respect to goals and help them to improve learning. This study was designed to explore the effect of descriptive feedback and corrective feedback on academic achievement of VII grade in mathematics. Only post-test control group design was used. There were three groups. Group 1 received descriptive feedback, group 2 received corrective feedback and group 3 served as a control group. All groups contained 53 students each. The results analysed indicated that descriptive feedback has more positive effect on students’ achievements as compare to corrective feedback. Students taught through corrective feedback performed better than control group. Although, it is difficult to generalize the results of this study (issue of all experimental researches) but having support of literature it might be suggested that feedback is effective tool for the improvement of mathematics achievement of the students